Discourse and democracy : critical analysis of the language of government - Farrelly, Michael, 1974- (Routledge critical studies in discourse, 2015)
"In this new study, Farrelly gives a critical examination of democracy as it is conceived and practiced in contemporary advanced liberal nations. The received wisdom on democracy is probelmatized through a close analysis of discourse in combination with critical theories of democracy and of the State. The central theme of the book is the paradox of pervasive reference to democracy as a legitimation of political action by liberal governments versus the converse weakening of actual democratic practice within the liberal world. Farrelly builds on the work of Fairclough and others to examine this paradox, developing a new critical concept of "democratism" as an ideology that undermines the possibility of a more genuine democracy through political actors who oversimplify the idea of democracy. The book includes critical analyses of key political texts taken from presidential and prime ministerial speeches from the US and UK that attach democracy to non-democratic practices"--